Technical Credit. - Gorton, Ian; Bucaioni, Alessio; Pelliccione, Patrizio (Communications of the ACM, 2025)
The author offers his opinion on balancing initial investment and long-term results in the software development process. He explains that technical debt (TD) often arises when short-term delivery goals are prioritized over long-term product concerns and explores the opposite of TD, technical credit (TC), which reduces development friction.